Comparison of Laser Fluorescence and Digital Radiograph with International Caries Detection and Assessment System in Primary Teeth (In-vivo study) - Kassab, Rana; Elsaad, Nayer Abo; Badr, Shiern (European Scientific Journal, ESJ, 2021)
Background: There has been an increased incidence of dental caries in children due to recent changes in lifestyle. More sensitive and reproducible diagnostic tools for precise caries detection in children are needed because of the complex occlusal anatomy. Aim: To compare the clinical performance and accuracy of international caries detection and assessment system-II (ICDAS II) versus DIAGNOdent pen and digital bitewing radiograph in the detection of occlusal caries in the primary teeth. Materials and Methods: Fifty children aged 6-11 years were assessed of both gender (29 girls and 21 boys) and 377 occlusal surface of primary teeth were examined by visual ICDAS II, DIAGNOdent pen and digital bitewing radiographic examination at D0 (non caries lesions), D1 (lesions limited to enamel) and D2 (lesions limited to dentin) thresholds. Results: Sensitivity at D0 for ICADS II was 14.23% and 95.95% for DIAGNOdent pen and 87.85% for digital bitewing, radiographs while specificity for both ICADS II and bitewing radiographs were 99.23% but 73.85% for DIAGNOdent pen. At D1, threshold sensitivity of ICADS II and digital bitewing radiographs were higher than DIAGNOdent pen but specificity for bitewing radiographs and DIAGNOdent pen 90.69% - 87.99%. were highly significant than ICADS II At D2, threshold specificity for all diagnostic methods was almost similar with better sensitivity for ICADS II and digital bitewing radiographs. Conclusion: This study showed that ICDAS II, Diagnodent pen, and bitewing radiography are effective for the detection of occlusal caries for primary molars. Digital bitewing radiography correlated stronger with ICDASII than Diagnodent pen and proved to be the best method to detect occlusal lesions within the dentin in primary molars while Diagnodent pen and bitewing radiography are better for detecting enamel caries lesion. In addition, the clinical performance of three diagnostic methods was insufficient to detect occlusal caries lesions separately. Consequently, it is advisable to use a combination of diagnostic methods, especially in unclear cases, as well as in cases of initial lesions and their monitoring.